Effects of cilostazol on the progression and regression of symptomatic intracranial artery stenosis: it reduces the risk of ischemic stroke - Wenhui Zhang; Fangfang Cai; Zhongmin Wen (Neural Regeneration Research, 2015)
OBJECTIVE: To assess the efficacy and safety of cilostazol on the progression and regression of symptomatic intracranial artery stenosis. DATA RETRIVAL: We searched the main databases for eligible trials including Medline (from 1966 to June 2014), Embase (from 1980 to June 2014), Cochrane Library (Issue 6, 2014), Chinese National Knowledge Infrastructure (from 1995 to June 2014), Current Controlled Trials (http://controlled-trials.com), Clinical Trials.gov (http://clinicaltrials.gov), and Chinese Clinical Trial Registry (http://www.chictr.org). All studies regarding prevention and treatment of symptomatic intracranial arterial stenosis by cilostazol were collected. The Mesh or text keywords were the English words: "cilostazol, phosphodiesterase 3 inhibitor, atherosclerosis, and ischemic stroke." No restrictions were put on publications or publication language. SELECTION CRITERIA: Grade A or B randomized controlled trials were selected according to the quality of evaluation criteria from the Cochrane Collaboration, in which cilostazol and aspirin were used to evaluate the effects of cilostazol in the treatment of patients with symptomatic intracranial artery stenosis. The quality of study methodology was evaluated based on criteria described in Cochrane Reviewer′s Handbook 5.0.1. RevMan 5.2 software was used for data analysis. MAIN OUTCOME MEASURES: Clinical efficacy and safety of cilostazol in stopping progression and promoting regression of symptomatic intracranial artery stenosis were measured by magnetic resonance angiography and transcranial Doppler. RESULTS: Two randomized controlled trials with a total of 203 patients were included in this study. The results showed that while cilostazol was associated with a significantly reduced progression of intracranial artery stenosis (OR = 0.21, 95%CI: 0.09-0.47, P < 0.01), it had no beneficial effect on symptom regression (OR = 1.42, 95%CI: 0.80-2.51, P = 0.24). During the follow-up period, although some adverse effects developed, including headache, gastrointestinal disturbance, and dizziness, incidences of bleeding were lower than in aspirin-treated patients. CONCLUSION: Cilostazol may prevent the progression of symptomatic intracranial artery stenosis, which could reduce the incidence of ischemic stroke.